Konstruksi Pemberian SP3 dalam Proses Penyidikan di Polres Wonosobo Studi Tahun 2022 - Gulden Wahyu Pratama; Hary Mulyadi (Transformasi Hukum, 2023)
This thesis aims to analyze the construction of the issuance of an Investigation Termination Warrant (SP3) in the investigation process at the Wonosobo Police by using an empirical juridical approach. SP3 is a legal instrument given by investigators to suspects to stop the process of investigating a case. The research method used is a case study method with a qualitative approach. Primary data was obtained through in-depth interviews with investigators in the process of granting SP3, as well as through direct observation of the investigation process at the Wonosobo Police. Secondary data was obtained from laws and regulations related to SP3, court decisions, and related literature. The results of the study show that the construction of the provision of SP3 at the Wonosobo Polres is influenced by several things, namely regarding the applicable laws and regulations, namely the Criminal Procedure Code (KUHAP). Law number 2 of 2002 concerning the police, as well as widening the direction of discretion in law enforcement efforts through the principles of restorative justice. So that the SP3 implemented in the Wonosobo Polres is not only based on justice and accountability of law enforcement but also fulfillment of community rights to more open access to law.